Patterns of foreign direct investment in Egypt: Descriptive insights from a novel panel dataset at the governorate level - Shima'a Hanafy (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This paper describes the main characteristics of Foreign Direct Investment (FDI) in Egypt using an unpublished dataset for FDI in 27 Egyptian governorates covering the period 1972 - 2009. Special attention is given to the geographical distribution of FDI, both as an aggregate and at the sectoral level. The paper is the first article of a larger empirical project on FDI in Egypt at the governorate level. Our dataset shows that FDI is unevenly distributed across Egyptian governorates. More than 60% of 'non-petroleum greenfield FDI' stock has been accumulated by two governorates, Cairo and Giza, and roughly 90% of FDI stock targets only 10 governorates. Tracing two spatial concentration indices of FDI inflows (Gini coefficient and coefficient of variation) over four decades, we find that the unequal geographical distribution of FDI decreased until the mid/late 1990s. This trend, however, did not continue when there was a substantial increase of FDI inflows in the 2000s. Moreover, we find differences in the degree of geographical concentration of FDI between various economic sectors. Service FDI shows the strongest concentration (mostly articulated in the ICT and finance sectors), while manufacturing FDI is the most geographically dispersed.
Keywords: F21; E22; R12; O53; Z10; 330; Foreign Direct Investment; sectoral FDI; regional FDI; Egypt